Physical Condition and Concentration on Pencak Silat Athletes - Salsaputri, Della; Sultoni, Kuston; Jajat; Ruhayati, Yati; Nur Ajid, Oktoviana (Journal of Sport Science and Fitness, 2025)
Introduction: Physical condition and concentration are key factors influencing the performance of pencak silat athletes in both fighter and artistic categories. However, the relationship between these two aspects has rarely been explored specifically in this sport. Objectives: This study aimed to compare physical condition and concentration levels between athletes in the fighter and artistic categories, and to examine the relationship between the. Method: A cross-sectional design was used involving 36 athletes (18 fighter and 18 artistic). Physical condition was assessed through power, speed, agility, and endurance tests, while concentration was measured using the Grid Concentration Test (GCT). Data were analyzed using independent samples t-tests and Pearson correlation. Result: The results showed that fighter athletes had significantly higher power, speed, and endurance (p < 0.05), whereas artistic athletes had significantly better agility (p < 0.05). No significant differences in concentration levels were found between the two groups (p > 0.05). Additionally, there was no significant correlation between physical condition and concentration in either group (p > 0.05). Conclusion: These findings suggest that physical and cognitive aspects may develop independently. Therefore, training programs should incorporate both components to enhance overall athlete performance.